Perkembangan Penelitian Tipografi: Kajian Bibliometrik - Santoso, Citra Fadillah (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
An essential component of visual communication design is typography. Moreover, research on typography has been done in the past from both the standpoints of study and creation. Yet, there has never been research done on examining the development trend of studies on the subject of typography. Therefore, the following research questions were addressed: (1) What are the trends in research productivity regarding to typography topics based on year, publication source, affiliation, country, citation, and authorship from year to year? and (2) How is the development of research themes regarding to typography research from year to year? To conducted the research question, this research used the bibliometric method. Based on the keyword